Globalization, Cosmopolitanism, and the New Generations: Growing Up with Global Ties - (:unkn) unknown (My University, 2014)
There is a notion that the rapid globalization of the recent decades results in more cosmopolitan outlooks among the people, specifically the new generations, around the world. Indeed, the new generations could become the agents for a generational change in that direction. Using the data from World Values Survey (WVS) along with blogs analysis and interviewing, this study asks whether or not the new generations are becoming more cosmopolitan. The results show that the new generations are more cosmopolitan in number, but more importantly, there is a qualitative difference between newer and older generations. The new generations' cosmopolitan experiences are more reflexive (experienced directly), while the older generations' cosmopolitanism is more objective (conceptual). There are also many variant forms of cosmopolitanism existing today. This study also tries to find a global methodology for social research and to get out of the limitations of traditional national frameworks.
Keywords: Belonging; Cosmopolitanism; Cultural Identity; Generational Change; Globalization; World Citizen